Underwater Routing Protocols: Analysis of Intrepid Link Selection Mechanism, Challenges and Strategies - Shahzad Ashraf; Aslam, Zeeshan; Yahya, Adnan; Tahir, Adnan (International Journal of Scientific Research in Computer Science and Engineering, 2020)
The sensor nodes deployed in underwater environment have a different routing mechanism in contrast to the terrestrial network. In order to get underwater information from dynamically deployed senor nodes, a smooth packet transmission must be maintained, which is a crucial challenge, and selecting the best communication link between source and destination node is a key phenomenon. The meticulous research has been conducted to search out the best link selection mythology of bodacious underwater routing protocol EnOR, SURS‐PES and USPF. The performance has been evaluated through NS2 simulation for packet delivery ratio, end-to-end delay, network lifespan and network energy consumption.